Faktor Lingkungan Rumah Dan Praktik Hidup Orang Tua Yang Berhubungan Dengan Kejadian Pneumonia Pada Anak Balita Di Kabupaten Kubu Raya Tahun 2011 - Dewi Sartika, Mas Henny; Setiani, Onny; Wahyuningsih, Nur Endah (Jurnal Kesehatan Lingkungan Indonesia, 2012)
Background : Pneumonia is one of respiratory tract infections that attacks a below part of a respiratory tract. AHealth Profile of Kubu Raya District in 2010 indicated that there were 545 pneumonia cases in 2009 and 276pneumonia cases in 2010 on children less than five years old. The objective of this research was to analyze therelationship between the factors of house environment and healthy behavior with the occurrence of pneumonia onchildren less than five years old in Kubu Raya District year 2011.Methode : This was observational-analytic research with Cross-Sectional approach. Population of this researchwas all children less than five years old who visited outpatient unit and suffered from pneumonia at HealthCenters in Kubu Raya District from January to August 2011. Number of cases and controls were 124. Data wereanalyzed using Chi-Square and Logistic Regression tests using SPSS 16.Result : The result of this research showed that the variables which had significant relationship with the occurrenceof pneumonia were: type of house roof (p value < 0.001), type of floor (p value < 0.001), index of house ventilation(p value = 0.012), and house density (p value = 0.006), habit of opening a window (p value = 0.001), habit ofwashing hands (p value = 0.004), habit of smoking inside a house (p value < 0.001), and habit of cleaning ahouse (p value < 0.001). As a suggestion, they need to replace their house roofs with metal material, change aconstruction of a house floor with a waterproof material, widen house ventilation, enlarge a room, open a windowfrom morning to afternoon, wash hands, not smoking inside a house, and clean a house.Key Words : House Environment, Healthy Behavior, Pneumonia